Penerapan Teknik Kolase Bahan Limbah dalam Meningkatkan Kreativitas Siswa Kelas Rendah di MI Tarbiyatul Khoirot Semarang - Wirda, Lia; Shanie, Arsan (Universitas Negeri Padang, 2023)
This research was motivated by the problem of students' low creativity, one of which was that children had difficulty finding solutions to problems given during learning. Apart from that, they also lack skills in conveying their opinions, both orally and in writing. This can be seen when carrying out tasks related to skills, especially making free forms from collage techniques of waste materials. Creativity is the result of interaction between an individual and his environment, the ability to create new combinations, based on data, information or elements that already exist or are previously known. This research aims to increase students' creativity by using collage techniques to create interesting works. The research method used is classroom action research which is carried out in four stages, namely planning, implementation and observation. The subjects of this research were 28 class 1A students at MI Tarbiyatul Khoirot Semarang. The researcher's data collection techniques used observation and interview techniques. The results of research in cycle I obtained a percentage of 31.6% for the criteria for children developing according to expectations, 56.7% for the criteria for children developing well, 14.2% for the criteria for children starting to develop. In cycle II, the percentage obtained was 97.2% for the criteria for children developing very well, 44.9% for the criteria for children developing well and 3.2% for the criteria for children still developing. From these results, it was concluded that creativity increased after collage activities were carried out using natural materials, paper which gave children the freedom to explore.